A third eye with human-computer interaction for the visually impaired. (April 2017) - Başçiftçi, Fatih; Eldem, Ayşe
Highlights: A new device was developed for visually impaired people. A blind person can read any document with his hands using this device. The device is ergonomic, portable, vocalizable, refreshable and multi-functional. The device's weight, cost and size features are too good. Abstract: In order to reduce dependency of the visually impaired people on others resulting from their visual impairment, an ergonomic, portable, vocalizable and refreshable Braille reader was developed. Texts from a scanned document or any text imported from a computer are transmitted to the device developed, enabling visually handicapped persons to read a text in the Braille format by using their hands. Some innovations were made in this study with a view to further reduce the size of the previously developed circuit and to lower the cost. The circuit for charging the device and the keypad for the button circuit were redesigned. A new circuit was created for the panels which enables data transfer to the Braille cells. The newly developed device has a reduced size by 57.94%, the cost of device development is cut by 40% and the weight of device has been reduced by 33.3%. Graphical abstract: